Analysis and design of the power law damping based on the nonlinear vessel isolation system. (December 2018) - Wang, You; Zhu, Xinghua; Zheng, Rong; Tang, Zhe; Chen, Bingbing
In this study, the applications of the cubic power law damping in vessel isolation systems are investigated. The isolation performance is assessed using the force transmissibility of the vessel isolation system, which is simplified as a multiple-degree-of-freedom system with two parallel freedoms. The force transmissibilities of different working conditions faced in practice are discussed by applying the cubic power law damping on different positions of the vessel isolation system. Numerical results indicate that by adding the cubic power law damping to an appropriate position, the isolation system can not only suppress the force transmissibility over the resonant frequency region but also keep the force transmissibility unaffected at the nonresonant frequency region. Moreover, the design of the nonlinear vessel isolation system is discussed by finding the optimal nonlinear damping of the isolation system.